The Relationship Between Services Quality and patient \'s loyalty in Tehran Public and Private Hospitals:2009 - SJ tabibi; MJ kakhani; MR Gohari; S shahri (Tehran University of Medical Sciences, 2010)
Background: the competitive of existing area in servicing organizations which are showing the desired services, the importance and satisfy customers and making content about their needs more than before. Material & Methods: The present study descriptive survey of practical purpose and its method correlation study has been done. Statistical Society of  this research is all referred patients to outpatient clinics in private and governmental hospitals at Tehran province(N=260). The data collecting tools have included two questionnaires, so for measuring of services quality was used from servqual standard questionnaire and part of parasoraman, zitamel and berry(1996) standard questionnaire about customer's behavioral tendencies for measuring of loyalty. Results: T-test was used  for comparing the average in private and governmental section at all the five dimentions and  pierson correlation coefficient was used for determining the relation between one by one the five dimentions of services quality with patient 's loyalty and also used regression  test. 36% of variance in patients' loyalty is due to components of service quality. A change of one unit in tangible factors, ensuring, and empathy results in 0.263, 0.285, and 0.116 change in patient 's loyalty, respectively. Regression model cannot make any prediction for other components because the significance levels of components are greater than 0.05. Conclusion: whereas in this research there is meaningful relation between services quality and patient's loyaltyit seems that in such organizations the strategic application which cause the improving of qualitywill redound the increasing of patient'sloyalty and finally it will cause more profitability for hospitals.